Other-initiations of repair in German Whats App chats. (April 2021) - Mostovaia, Irina
Abstract: This paper takes a conversation analytic approach to investigate how interlocutors deal with different kinds of interactional problems occurring in German text-based communication on Whats App. The data analyzed in the present study is obtained from the Mobile Communication Database 1 (http://mocoda.spracheinteraktion.de ) and Mobile Communication Database 2 (https://db.mocoda2.de ). Focusing on other-initiations of repair, this article shows that interlocutors indicate trouble sources in the preceding messages sent by their communication partners in two ways: On the one hand, writers use a wide range of other-initiations transferred from German spoken language, such as question words ( was 'what', wer 'who', etc.) or candidate understandings in the form of Meinst du X? ('Do you mean X?', cf. Schegloff et al., 1977 ). On the other hand, interlocutors may display an interactional problem by deploying particular resources that the medium provides, such as asterisks, equal signs, question marks, etc. (see also Busch, in this collection of articles). A close examination of other-initiations of repair in Whats App chats thus provides an insight into how the different formats mentioned above are used, especially in relation to (a) the different types of trouble sources occurring in text-based Whats App chats, and (b) the general communication conditions created by the medium. Moreover, it will be discussed how different formats of other-initiation of repair shape the negotiation of responsibility for the trouble source or the repair proper, manage epistemic rights and contribute to the face work in the sense of Goffman (1967) .